2014
DOI: 10.1002/anie.201405199
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of I2 by Macrocyclic Polyazadithiophenolato Complexes Mediated by Charge‐Transfer Interactions

Abstract: The macrocyclic complex [Ni2(L)(OAc)]ClO4 (1) adsorbs up to 17 molar equivalents (>270 wt%) of iodine, although it does not exhibit permanent porosity. Vibrational spectroscopic and crystallographic studies reveal that two I2 molecules are captured by means of thiophenolate→I2 charge-transfer interactions, which enable the diffusion and sorption of further I2 molecules in a polyiodide-like network. The efficient sorption and desorption characteristics make this material suitable for accommodation, sensing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The plots of time versus absorbance (inset of Figure 3b)o fi odine monitored at the 288 nm show the release kinetics of sample 1@I 2 , 2@I 2 and 3@I 2 .A fter 24 h, about 224, 254 and 274 mg of I 2 were captured by 1gof their corre- sponding crystalso f1@I 2 , 2@I 2 and 3@I 2 ,r espectively.A fter the uptake and release processes, the crystallizability and structural integrity of isomers 1-3 was well-preserved and validated by PXRD measurements. [19] The bond lengths of I1-I4 and I2-I3 from {Cu 2 I 2 }d imers andi odine molecules were 3.698 and 3.277 ,r espectively.A dditionally,t he angles of I1-I4-I3 and I2-I3-I4 arranged linearly and had values of 164.088 and 169.268,r espectively.M ore important, the bond length of Cu-I and the angle of Cu-I-Cu form the {Cu 2 I 2 }d imers increased significantly,i ndicating the presence of strong chemical interactions between adsorbed iodine and the sorptions ites of {Cu 2 I 2 } dimer.Acombination of experimental results and structural analyses led to two main conclusions:t he {Cu 2 I 2 }d imers in our present case may act as sorption sites for iodine capture,a nd the differentc apabilities for iodine capture were attributed to the distorted pores or channels, since as-synthesized isomers 1-3 had the same ratio of {Cu 2 I 2 }d imer-sorption sites within the inner surfaces of their frameworks. [18] In this sense,aguest-induced single-crystalt ransformation may supply ad irect way to analyze the structure-property relationship betweens uch sorptions ites and retained iodine molecules, leadingt oabetteru nderstanding of the dynamic iodine capturep rocess.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The plots of time versus absorbance (inset of Figure 3b)o fi odine monitored at the 288 nm show the release kinetics of sample 1@I 2 , 2@I 2 and 3@I 2 .A fter 24 h, about 224, 254 and 274 mg of I 2 were captured by 1gof their corre- sponding crystalso f1@I 2 , 2@I 2 and 3@I 2 ,r espectively.A fter the uptake and release processes, the crystallizability and structural integrity of isomers 1-3 was well-preserved and validated by PXRD measurements. [19] The bond lengths of I1-I4 and I2-I3 from {Cu 2 I 2 }d imers andi odine molecules were 3.698 and 3.277 ,r espectively.A dditionally,t he angles of I1-I4-I3 and I2-I3-I4 arranged linearly and had values of 164.088 and 169.268,r espectively.M ore important, the bond length of Cu-I and the angle of Cu-I-Cu form the {Cu 2 I 2 }d imers increased significantly,i ndicating the presence of strong chemical interactions between adsorbed iodine and the sorptions ites of {Cu 2 I 2 } dimer.Acombination of experimental results and structural analyses led to two main conclusions:t he {Cu 2 I 2 }d imers in our present case may act as sorption sites for iodine capture,a nd the differentc apabilities for iodine capture were attributed to the distorted pores or channels, since as-synthesized isomers 1-3 had the same ratio of {Cu 2 I 2 }d imer-sorption sites within the inner surfaces of their frameworks. [18] In this sense,aguest-induced single-crystalt ransformation may supply ad irect way to analyze the structure-property relationship betweens uch sorptions ites and retained iodine molecules, leadingt oabetteru nderstanding of the dynamic iodine capturep rocess.…”
Section: Resultsmentioning
confidence: 95%
“…The bond length of I3-I4 from iodine molecules was 2.794 larger than that of free iodine (2.667 ). [19] The bond lengths of I1-I4 and I2-I3 from {Cu 2 I 2 }d imers andi odine molecules were 3.698 and 3.277 ,r espectively.A dditionally,t he angles of I1-I4-I3 and I2-I3-I4 arranged linearly and had values of 164.088 and 169.268,r espectively.M ore important, the bond length of Cu-I and the angle of Cu-I-Cu form the {Cu 2 I 2 }d imers increased significantly,i ndicating the presence of strong chemical interactions between adsorbed iodine and the sorptions ites of {Cu 2 I 2 } dimer.Acombination of experimental results and structural analyses led to two main conclusions:t he {Cu 2 I 2 }d imers in our present case may act as sorption sites for iodine capture,a nd the differentc apabilities for iodine capture were attributed to the distorted pores or channels, since as-synthesized isomers 1-3 had the same ratio of {Cu 2 I 2 }d imer-sorption sites within the inner surfaces of their frameworks.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The structure and composition of the host determine the intermolecular interactions responsible of the capture/release mechanisms. In various MOFs, for instance, iodine capture is based on halogen bond interactions with metal centers or building blocks of the framework, which often produce (poly) iodide moieties ,,. In particular, a recent single‐crystal X‐ray study showed that I 2 molecules were incorporated formally as I 4 2− anions in a Cu−MOF thanks to strong I − ⋅⋅⋅I 2 ⋅⋅⋅I − interactions with the {Cu 4 I 4 } n chains of the host.…”
Section: Organization Of Dihalogens In 1d Channelsmentioning
confidence: 99%
“…The environmental relevance of toxic gas capture and the electric conductivity enhancement caused by iodine uptake, have raised great interest on the incorporation of dihalogen molecules in diverse hosts like clathrasils,, zeosils,, and ALPOs, but also organic salts, organic zeolites, Hofmann clathrates,, and other MOFs …”
Section: Organization Of Dihalogens In 1d Channelsmentioning
confidence: 99%